Redo Transanal Soave Pull Through with or without Assistance in Hirschsprung Disease: An Experience in 46 Patients - Peng, Chunhui; Chen, Yajun; Pang, Wenbo; Zhang, Tingchong; Wang, Zengmeng; Wu, Dongyang; Wang, Kai (European Journal of Pediatric Surgery, 2020)
Introduction Transanal Soave pull through (PT) with or without assistance can be performed as a redo procedure for Hirschsprung disease (HD). In this study, we reviewed the indications and clinical outcomes of redo transanal Soave with or without assistance.Materials and Methods A retrospective analysis was performed on patients who underwent redo transanal Soave with or without assistance in our hospital from 2004 to 2016, and did not have rectourethral fistula or rectovaginal fistula. The Krickenbeck classification system was used to evaluate postoperative bowel function. We analyzed the associated factors of the two main indications.Results In this study, 46 patients were included, representing 5.6% of all HD PTs; 42 patients were initially operated elsewhere and 4 at our hospital. Primary PT surgeries included 38 transanal Soave, 2 Rehbein, 1 Martin, and 5 unknown procedures. The indications for redo PT were residual aganglionosis/transition zone PT (RA/TZPT) (27, 58.7%), anastomotic complication (14, 30.4%), and dilated distal segment (5, 10.9%). The median age of these 46 patients at primary and redo PT was 7.0 months (range, 0.4–137 months) and 45.5 months (range, 7–172 months), respectively. All 46 patients underwent redo transanal Soave PT; 43 patients (93.5%) underwent transanal Soave with laparotomy (n = 42) or laparoscopy (n = 1), and another 3 patients underwent transanal Soave PT. Six patients (13%) experienced complications within 30 days after redo surgery. A total of 43 patients were followed up, and the median follow-up period was 100 months (range, 35–180 months). Two patients could not hold back defecation in some inconvenient conditions. Sixteen patients (37.2%) had soiling, and 8 (18.6%) of 16 patients complained frequent soiling occurrence (more than 1/week). Only one patient complained of constipation (grade 1). Patients with anastomotic complication had more early postoperative complication and higher rate of soiling than patients with RA/TZPT, but there was no statistical difference (p = 0.672 and p = 0.105).Conclusion Transanal Soave PT with or without assistance was effective in resolving different problems after initial PT, while soiling was the most common postoperative problem, especially patients with anastomotic complication.
Keywords: Hirschsprung disease; indication; redo pull through; transanal Soave; soiling